STRATIGRAPHY AND STRUCTURAL PECULIARITIES OF THE LOWER PALEOZOIC CARBONATE-SILICEOUS-TUFFACEOUS COMPLEX OF THE CHINGIZ RANGE (EASTERN KAZAKHSTAN) - Degtyarev K.E.; Dubinina S.V.; Orlova A.P. (My University, 1999)
Sections of the Middle Cambrian-Middle Ordovician carbonate-siliceous-tuffaceous complexes of eastern Kazakhstan, which are characterized by different groups of fossils (conodonts, graptolites, brachiopods, trilobites), are described for the first time. The heterofacies sections are subdivided into two types. They are first established to occupy an intermediate position in the structural-facies zonation of Chingiz Range, between volcanosedimentary and siliceous-basaltic sequences. It is inferred that the carbonate-siliceous-tuffaceous deposits presumably accumulated in a marginal part of a back-arc basin in the vicinity of a volcanic island arc.
Keywords: Paleozoic; Paleozoic; Палеозой